Telomere Shortening in Peripheral Leukocytes Is Associated With Poor Survival in Cancer Patients Treated With Immune Checkpoint Inhibitor Therapy - Rolles, Benjamin; Gorgulho, Joao; Tometten, Mareike; Roderburg, Christoph; Vieri, Margherita; Abels, Anne; Vucur, Mihael; Heymann, Felix; Tacke, Frank; Brümmendorf, Tim H.; Luedde, Tom; Beier, Fabian; et al. (Frontiers in Oncology, 2021)
Background: Immune checkpoint inhibitor (ICI) therapy represents a new standard of care for an increasing number of malignancies. Nevertheless, response rates and outcome of ICI treatment vary between individuals and the identification of predictive markers or hints towards immune cell exhaustion during therapy has remained a major challenge. Leukocyte telomere length is an established predictive biomarker of replicative aging and cellular proliferative potential in various hematological diseases. However, its role in the context of ICI therapy has not been investigated to date. Here, we analyze the age-adapted delta telomere length (ΔTL) of peripheral leukocytes as a potential predictive and prognostic marker in patients undergoing ICI therapy. Methods: Age-adapted delta telomere length (ΔTL) of 84 patients treated with ICIs for solid malignancies was measured via quantitative real-time PCR. ΔTL was correlated with outcome and clinical data. Results: ΔTL was not significantly altered between patients with different tumor entities or tumor stages and did not predict tumor response to ICI therapy. However, ΔTLs at initiation of treatment were a prognostic marker for overall survival (OS). When using a calculated ideal cut-off value, the median OS in patients with shorter ΔTL was 5.7 months compared to 18.0 months in patients showing longer ΔTL. The prognostic role of age-adapted ΔTL was further confirmed in uni- and multivariate Cox-regression analyses. Conclusion: In the present study, we demonstrate that patients with shorter telomere length in peripheral blood leukocytes are associated with a significantly impaired outcome in patients receiving ICI therapy across different malignancies. We explain our findings with a hypothetical older replicative age reflected by a premature TL shortening. Further follow-up studies are needed to provide insides about the exact mechanism how shortened telomeres eventually affect OS and could help guiding therapeutic decisions in future.